THE IMPORTANCE OF MATHEMATICAL STATISTICS IN MEDICINE AND BIOLOGY - Aliyev Nurillo Abdiqayumovich,; Yoqubova Umida Alisher qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This thesis examines the significant role of mathematical statistics in the fields of medicine and biology. Statistical methods are essential for analyzing clinical research, evaluating treatment effectiveness, studying biological processes, and predicting disease spread. The study highlights the use of descriptive and analytical statistical methods, correlation and regression analysis, and probability-based modeling in medical and biological research. The findings demonstrate that mathematical statistics improves data accuracy, supports evidence-based decision-making, enhances early diagnosis, and contributes to the development of personalized medicine. Furthermore, with the rapid advancement of digital technologies, artificial intelligence, and big data, the importance of statistical methods continues to grow in modern healthcare and biological sciences.